Hit refresh : the quest to rediscover Microsoft's soul and imagine a better future for everyone /: the quest to rediscover Microsoft's soul and imagine a better future for everyone. (2017) - Nadella, Satya; Shaw, Greg; Nichols, Jill Tracie
No abstract available